2021
DOI: 10.3389/fphys.2021.668327
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Exercise on Exhausted and Senescent T Cells: A Systematic Review

Abstract: The impaired effector function of exhausted and senescent T cells is implicated in cancer progression and inadequate vaccine responses. Exercise has been shown to improve cancer therapy and vaccine efficacy, most likely by improving immune function. However, given inconsistent terminology and definitions, the interactions between exercise and exhausted and senescent T cells remain unclear. We therefore performed a systematic review to investigate the effect of exercise on senescent and exhausted CD8+ T cell po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…While conventional T cell mobilization appears to be unimpaired after acute exercise, alterations in CD57 and perforin may have functional implications. We report an increase in CD8 + CD57 + counts post-exercise, which is consistent with previous work in healthy men ( 42 ) as acute exercise generally increases mobilization of senescent (CD28 − CD57 + ) T cells ( 43 ). In contrast, the frequency of CD8 + CD57 + cells was unchanged, with a non-significant 6.6% decrease at 0H.…”
Section: Discussionsupporting
confidence: 92%
“…While conventional T cell mobilization appears to be unimpaired after acute exercise, alterations in CD57 and perforin may have functional implications. We report an increase in CD8 + CD57 + counts post-exercise, which is consistent with previous work in healthy men ( 42 ) as acute exercise generally increases mobilization of senescent (CD28 − CD57 + ) T cells ( 43 ). In contrast, the frequency of CD8 + CD57 + cells was unchanged, with a non-significant 6.6% decrease at 0H.…”
Section: Discussionsupporting
confidence: 92%
“… 102 A systematic review of studies including RCT demonstrated a beneficial effect of repeated aerobic exercise or endurance resistance training on CD28 expression of CD8 + T cells irrespective of age or level of sedentarism. 103 This occurred despite a temporary increase in senescent CD8 + CD28 null T cells immediately postexercise. 103 Cardioprotective drugs such as lipid‐lowering statins have pleiotropic effects, which include a lowering of circulating CD4 + CD28 null T cells.…”
Section: Introductionmentioning
confidence: 99%
“… 103 This occurred despite a temporary increase in senescent CD8 + CD28 null T cells immediately postexercise. 103 Cardioprotective drugs such as lipid‐lowering statins have pleiotropic effects, which include a lowering of circulating CD4 + CD28 null T cells. 6 , 29 This is likely related to anti‐inflammatory properties and pro‐apoptotic effects on senescent T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Turner et al ( 12 ) demonstrated a greater increase in late differentiated CD27-CD28- CD8+ T-cells following 60 min of vigorous running exercise than less differentiated cells. CD28-CD57+ T-cells are also significantly mobilized by exercise ( 13 ). This selective mobilization of later differentiated T-cells is due to the greater expression of type 2 beta-adrenergic receptors by highly differentiated T-cells, as epinephrine binding to these receptors promotes cell extravasation into the bloodstream ( 11 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…While TM T-cells are prevalent in healthy human subjects and are functionally distinct from CM and EM ( 3 ), their response to exercise has not been reported. Given the enhanced effector properties of TM relative to CM, the enhanced proliferative capacity of TM relative to EM, and the fact that TM T-cells comprise a substantial portion of the T-cells present in the blood ( 5 ), describing the mobilization of these cells by acute exercise is important to fully understanding the changes in T-cells that occur with exercise Further, while CD28-CD57+ T-cells are known to be mobilized by exercise ( 13 ), their relative mobilization compared to later differentiated subsets (EM, EMRA) lacking CD57 is not yet known. Finally, to our knowledge, there are no reports of the mobilization of CD28 + CD57+ T-cells with exercise.…”
Section: Introductionmentioning
confidence: 99%